ON SYSTEMS OF GENERATORS OF AUTOMATON PERMUTATION GROUPS - Сікора, Віра (SWorldJournal, 2022)
Systems of induced generating actions of automaton permutation groups on words of length r are investigated. A family of irreducible systems of generators is constructed, and the cardinality of such systems is found to be related with r. The theorem is pr